Penerapan Model CIRC (Cooperative Integrated Reading and Composition) dalam Meningkatkan Kemampuan Membaca pada Pembelajaran Bahasa - Lulut Yatmiatun; Ismiyati Haniah; Sri Karyati; Nur Astu Dwi Rahma; Sri Handayani Dwi Astuti; Endang Sulandari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Reading skills in the learning process are essential for academic development and life skills. One instructional model designed to foster these skills is the CIRC (Cooperative Integrated Reading and Composition) learning model. The purpose of this study is to describe the steps, advantages, and disadvantages of implementing the CIRC learning model in language learning. This study employs a qualitative approach. The research subjects are teachers. The informants in this study are language teachers. The data collection techniques used include interviews, observations, and documentation. The research findings are as follows:1) The steps in the CIRC model include the teacher initially explaining the learning material, forming groups, providing texts, silent reading, group discussions, group presentations, summarizing, writing, peer editing, revision, and publication; 2) The advantages of the CIRC model include improving students' critical thinking skills in solving problems, reducing teacher dominance in learning, motivating students to be meticulous, enabling students to understand meanings and check each other's work, enhancing learning outcomes, and creating an engaging learning atmosphere; 3) The disadvantages of the CIRC model include requiring a significant amount of time, difficulty in classroom management, the dominance of active students, and limited learning materials. The conclusion of this study is that the CIRC model can be applied in the learning process as an effort to enhance students' problem-solving skills during the learning process. Additionally, the CIRC model has proven to be effective in improving students' language skills in Madrasah Tsanawiyah or Junior High School level.